Global Consumer Culture and Halal Consumption: Insights from Indonesian Youth - Putra, Yudho Novandhika; Dewantara, Norman; Noer, Lissa Rosdiana (Halal Research, 2025)
The halal market is expanding rapidly, driven by the growing Muslim population. At the same time, young Muslims are experiencing changes in their consumption habits as they engage more with global trends. This study explores how acculturation to global consumer culture (AGCC) interacts with ethnic identity (EID) in shaping their choices between halal and non-halal products. A survey of 123 young Muslim respondents in Indonesia was conducted, and the data were analyzed using Structural Equation Modeling (SEM). The results show that exposure to global consumer culture does not weaken ethnic identity. Instead, young Muslims develop a bicultural identity, maintaining their commitment to halal consumption while embracing global influences. These findings highlight the need for businesses to adopt localization or glocalization strategies to better connect with Muslim consumers. Policymakers should also ensure that the halal market continues to evolve while staying true to Islamic values and meeting modern consumer needs.